LPS‐Induced Inflammation Prior to Injury Exacerbates the Development of Post‐Traumatic Osteoarthritis in Mice. (3rd August 2020) - Mendez, Melanie E; Sebastian, Aimy; Murugesh, Deepa K; Hum, Nicholas R; McCool, Jillian L; Hsia, Allison W; Christiansen, Blaine A; Loots, Gabriela G
ABSTRACT: Osteoarthritis (OA) is a debilitating and painful disease characterized by the progressive loss of articular cartilage. Post‐traumatic osteoarthritis (PTOA) is an injury‐induced type of OA that persists in an asymptomatic phase for years before it becomes diagnosed in ~50% of injured individuals. Although PTOA is not classified as an inflammatory disease, it has been suggested that inflammation could be a major driver of PTOA development. Here we examined whether a state of systemic inflammation induced by lipopolysaccharide (LPS) administration 5‐days before injury would modulate PTOA outcomes. RNA‐seq analysis at 1‐day post‐injury followed by micro‐computed tomography (μCT) and histology characterization at 6 weeks post‐injury revealed that LPS administration causes more severe PTOA phenotypes. These phenotypes included significantly higher loss of cartilage and subchondral bone volume. Gene expression analysis showed that LPS alone induced a large cohort of inflammatory genes previously shown to be elevated in synovial M1 macrophages of rheumatoid arthritis (RA) patients, suggesting that systemic LPS produces synovitis. This synovitis was sufficient to promote PTOA in MRL/MpJ mice, a strain previously shown to be resistant to PTOA. The synovium of LPS‐treated injured joints displayed an increase in cellularity, and immunohistological examination confirmed that this increase was in part attributable to an elevation in type 1 macrophages. LPS induced the expression of Tlr7 and Tlr8 in both injured and uninjured joints, genes known to be elevated in RA. We conclude that inflammation before injury is an important risk factor for the development of PTOA and that correlating patient serum endotoxin levels or their state of systemic inflammation with PTOA progression may help develop new, effective treatments to lower the rate of PTOA in injured individuals. © 2020 The Authors. Journal of Bone and Mineral Research published by American Society for Bone and Mineral Research.